Ceramic Prostethics Restaurations - Clinical Study - Zaharia Agripina; Stefanescu Corina; Davidescu Carolina; Murinean Rodica (Romanian Society of Oral Rehabilitation, 2009)
Purpose: This study seeks to create a systematic approach in choosing the right ceramic system according to the clinical situations. Material and method: The clinical cases have been selected from the Ovidius University of Constanta, Faculty of Dentistry's Prosthetic Clinic: two male patients and three female patients, between ages of 20 and 44, presenting coronary lesions and small partial edentations that required aesthetical and morpho-functional restorations by fixed ceramic prostheses manufactured according to standard protocols. Results: Following the choosing criteria for the ceramic system mainly suited to the clinical situation, led to obtainment of aesthetic and functional ceramic fixed prosthetics restorations, to the patients delight and satisfaction of the technician-dentist team. Conclusions: Choosing the proper ceramic systems depends on the minute evaluation of the patient's occlusion, decisions taken favoring aesthetics, resistance, bonding requirements and parafunctional situations, than on a preferred system. Dentists will select ceramic crowns by using hierarchical approach.